2017
DOI: 10.3389/fpsyg.2017.01798
|View full text |Cite
|
Sign up to set email alerts
|

Imagined Steps: Mental Simulation of Coordinated Rhythmic Movements Effects on Pro-sociality

Abstract: Rhythmically coordinating with a partner can increase pro-sociality, but pro-sociality does not appear to change in proportion to coordination success, or particular classes of coordination. Pro-social benefits may have more to do with simply coordinating in a social context than the details of the actual coordination (Cross et al., 2016). This begs the question, how stripped down can a coordination task be and still affect pro-sociality? Would it be sufficient simply to imagine coordinating with others? Imagi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 41 publications
1
24
0
Order By: Relevance
“…One reason for the differences in generalized pro-sociality seen in the Reddish et al (2014) experiments might actually be decreased generalized pro-sociality post-control. Experiment 1 of Cross et al (2017) suggested that certain control tasks might be capable of affecting cooperation in the opposite way to CRM (i.e. reducing cooperation).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…One reason for the differences in generalized pro-sociality seen in the Reddish et al (2014) experiments might actually be decreased generalized pro-sociality post-control. Experiment 1 of Cross et al (2017) suggested that certain control tasks might be capable of affecting cooperation in the opposite way to CRM (i.e. reducing cooperation).…”
Section: Discussionmentioning
confidence: 99%
“…The group cohesion items were taken from a similar study (Cross et al, 2017), and measured how similar and how close people felt to each other, how much they liked each other, and how much they wanted to see each other again. The participants answered all the items for each individual and for the experimental cohort as a whole.…”
Section: Group Cohesion Scalementioning
confidence: 99%
See 3 more Smart Citations